Flexible Business Models A Concept for Furniture Production Systems - Sorin BURDUCEA; Miron ZAPCIU (Communications of International Proceedings, 2022)
Highly customized products are what every client seeks. Each has its own preferences and needs to express its individuality in its own unique way. Furniture not only brings comfort and utility, but also shapes the environment we live in. It has always been a key element in our wellbeing, promoting our own lifestyle, just as much as clothing does. Tailor made clothing is part of our daily life, but not so much so when it comes to furniture. As furniture production facilities employ dozens of people and classical machinery, the only effective way in which they may operate is following rigid production procedures. The outcome is mass produced items with little to no customizable features. Flexibility is the main aspect of Industry 4.0 concept and using its ideas one may restructure the production environment to such an extent that mass produced individualized items are made possible. The change should employ besides advanced information technology concepts, a new breed of machinery as well. The new machinery needs to be as flexible, as movable, as transparent, as coherent, and as powerful as the information technology itself. Little has been written on how the machinery itself needs to change, apart from its IT controls, and what the vast implication arises at business level. By analyzing production processes and machinery along with client behavior, this paper brings in foreground some of the benefits of using an ultra-flexible production system and how this may help European furniture industry to claim back volume from Asian competitors.
Keywords: business model; production system; furniture; industry 4.0